Posthumanism: Towards a Relational Environmental Governance in the El Zarza Wildlife Refuge - Massa-Sanchez, Priscilla (Journal of Posthumanism, 2025)
This article analyzes environmental governance in the El Zarza Wildlife Refuge, Ecuador, through a posthumanist and decolonial lens. Using a situated qualitative approach, it critiques hierarchical and anthropocentric conservation models that have historically neglected both posthumanist relations and ancestral knowledge systems.The research reveals that in El Zarza, alternative forms of territorial governance are emerging—ones that recognize nature not merely as a resource but as a constellation of beings with voice and agency. These practices involve emotional and spiritual ties to the environment—such as forest care or respect for water cycles—and actively resist extractivist logics that impose external models of development. This resistance takes shape as epistemic resistance, affirming forms of knowledge and life historically devalued by dominant paradigms.Based on interviews, participant observation, and documentary analysis, this study invites a reconceptualization of conservation as a relational and ethical practice, embedded within multispecies networks where all beings have a role in shaping the territory.